SCIENCE IMAGE: A STUDY WITH TEACHERS FROM LUANDA - Victor, Eufrásia; Costa, Maria; Mendonça, Alice; Bonito, Jorge (Centro de Investigação em Educação da Universidade da Madeira, 2020)
Epistemology and the history of science play an important role in detecting learning disabilities in a given field of knowledge and in directing strategies for their elimination. This quantitative study aimed to understand the perceptions of 26 teachers working in a Luanda school about the image of science. A questionnaire based on INPECIP by Martín del Pozo was applied. The image of science that teachers convey varies between a rationalist and an empiricist view, and some do not effectively reveal the image of science they convey to their students. In a finer analysis, conceptions linked to a model of epistemological relativism, which considers scientific knowledge as the product of the interaction between thought and reality. Error is also understood as a starting point for new theories and, as a result, play an important role in the advancement of science.
Keywords: Science image; teachers; empiricism; rationalism; epistemological obstacles